The design and use of continuous GNSS reference networks - Avcı,Özgür. (Thesis (M.S.)-Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2007., 2007)
Today, through the developments in positioning technologies, coordinate information has been the information to which daily users who are not geodesists are frequently applied. Global Navigation Satellite Systems (GNSS), gives answer to the question "Where?" by defining the Earth on a reference system Vlith the help of recent investments and future aspects of GNSS systems wide range of users trust on the reliability and accuracy of position information achieved from these systems. In order to increase the accuracy of satellite based positioning systems to centimeter levels for the end users, Countries are establishing regional and local Continuously Operating Reference Stations (CORS) stations. These stations serve to satisfy high accurate position requirement of daily users, besides they are used for the studies like disaster management, transportation planning, detection of crustal movements and monitoring critical structures. In this study, the properties of GNSS with its future aspects, benefits of using all GNSS systems together, components required for system implementation and fields of use are presented with the proposals for the design of such systems. All components required for the CORS system are examined in two groups. First one is sites to which GNSS stations are installed and the other one is control center. Besides, the system is explained in details with its components in the scope of present technologies and techniques. The application of CORS systems are classified as R TK based applications, structural monitoring and crustal defOlwation. The benefits of using CORS system is mentioned, and proposals are given by regarding the technical properties of site equipments, the range of the application, economy and efficiency ofthe system. Examples from different studies are given in order to improve the quality and efficiency of ongoing projects and new project in different range.
Keywords: Global Positioning System.; Artificial satellites in navigation.